The dark calling - Cole, Kresley (Cole, Kresley. Arcana chronicles., 2018)
"When Evie receives life-changing - and possibly game changing - news, she has trouble believing it. Why doesn't she feel any different? Is it possible someone she trusts might by lying? Tensions seethe inside the castle of lost time as Evie starts to doubt her own sanity. Answers can be found outside their stronghold, but will Death help her find them - or prevent her from learning the truth about her future and Jack's possible survival? A mysterious, sinister power begins to affect the Arcana in its path. Forced out into the wasteland alone, Evie must depend on unexpected allies. But as a battle with Richter looms, can her new alliance defeat the Dark Calling before hell reigns on earth?" - Page [4] of cover.